Uporaba sinhrotronske svetlobe pri študiju strukture proteinov - Jenko, Saša (Vakuumist, 2002)
Synchrotron radiation has become a major structural research tool across the world in numerous scientific areas. It is a critical component for many of these developments, and it is essential for high-throughput crystallography. The source characteristics of modern synchrotrons are ideally matched to a number of difficult problems im macromolecular crystallography. Recent studies on viruses, membrane proteins and ribosomes give clear examples of the power of modern macromolecular crystallography using synchrotrone radiation. The detailed structural information obtained enables the relationship between structure and function to be addressed with confidence.
Keywords: sinhrotronsko sevanje; proteini; struktura